1998
DOI: 10.4319/lo.1998.43.5.0859
|View full text |Cite
|
Sign up to set email alerts
|

A light-scattering matrix for unicellular marine phytoplankton

Abstract: This paper presents angular and spectral measurements of the functions that create a scattering matrix (Mtiller matrix). The investigations were carried out on monocultures of the unicellular phytoplankton ChZoreZEa vulgar-is, ChZoreZZu kesleri, and Chroococcus minor at scattering angles from 8" to 155" and at wavelengths of 488, 514, and 633 nm. Living cultures of phytoplankton as well as cultures treated chemically (boiled in 5% NaOH) and physically (ultrasound) were tested. These treatments alter the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 10 publications
3
23
0
Order By: Relevance
“…Similar to other studies citing the importance of intracellular structure on the scattering matrix (e.g. QuinbyHunt et al, 1989;Witkowski et al, 1998;Svensen et al, 2007), these features have been speculatively attributed to gas vacuoles. The same studies used a population of homogeneous spheres using Lorenz-Mie theory to attempt to fit the measurements (n = 1.04, n = 0.000).…”
Section: The Influence Of Gas Vacuolation On the Vsfsupporting
confidence: 63%
“…Similar to other studies citing the importance of intracellular structure on the scattering matrix (e.g. QuinbyHunt et al, 1989;Witkowski et al, 1998;Svensen et al, 2007), these features have been speculatively attributed to gas vacuoles. The same studies used a population of homogeneous spheres using Lorenz-Mie theory to attempt to fit the measurements (n = 1.04, n = 0.000).…”
Section: The Influence Of Gas Vacuolation On the Vsfsupporting
confidence: 63%
“…Differences in the scattering properties of the other species may be explained by the work of Volten et al (1998) and Witkowski et al (1998), who demonstrated that vacuoles and other internal structures can significantly affect scattering. For example, the lower scattering of perpendicular polarization by I. galbana in the middle angles is likely due to its relative lack of internal structures.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Slade and Boss (2006) and Agrawal (2005) consider forward angles ,20u, whereas Vaillancourt et al (2004) and Ulloa et al (1994) study primarily backscattering. Large-angle experiments have been performed, of course: Volten et al (1998) covers intermediate angles between 20u and 160u, Witkowski et al (1998) looked at the large-angle scattering matrix for a single species, and Shao et al (2006) recently presented compelling theoretical as well as experimental results in the 40u to 140u range (albeit without considering polarization effects). Chami et al (2006) discuss spectral aspects of scattering at large angles.…”
mentioning
confidence: 99%
“…However, in contrast to other inherent optical properties, such as the absorption and beam attenuation coefficients, the volume scattering function has not been routinely measured and the existing measurements are typically limited in terms of spectral and angular coverage. A significant portion of available data of βψ; λ for natural waters [6][7][8][9][10][11][12][13][14][15][16][17], and for various particle types such as phytoplankton species and sediment particulate assemblages [18][19][20][21][22][23][24] was obtained with custom-built prototype instrumentation. For example, among the most commonly used sets of βψ measurements that represent oceanic and coastal waters are those documented in [6].…”
Section: Introductionmentioning
confidence: 99%